From Flor to Mary Jane divergences, intersection and trajectories - Olalia, Edre U. (UP DGO monograph series, 2017)
Although the cases of Flor Contemplacion and Mary Jane Veloso crept into the national consciousness under radically different circumstances, both of their narratives fundamentally show the culpability of a decrepit socio-economic system that has pushed millions of poor Filipinos to seek perceived better opportunities abroad. In turn, however, their struggles have ushered various insights into how similar cases can be more effectively handled by progressive people's organizations and lawyers' groups in the future with the view of ending the iniquitous labor-export policy of the government.